The Impact of Using Sevima Edlink E-Learning as A Media For Indonesian Language Learning - Pitaloka, Novita Dyah; Mawarsih, Putri Beny; Mustaji, Mustaji; Mariono, Andi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aim of the current research is to describe and examine the impact of using Sevima Edlink e-learning as a medium for learning Indonesian at the junior high school level. The research method used in the current research is a qualitative method using a case study approach.. The data collected used observation and interviews with the aim of obtaining information about teacher and students’ experiences regarding digital-based learning media. The primary data used is a description of the use of the Sevima Edlink application in Indonesian language learning activities. Secondary data is in the form of literature studies originating from books, articles, proceedings, theses and other media. The data that has been collected will be analyzed according to the discussion of related topics using data reduction, presentation and conclusion methods. The research results show that students prefer the learning process using digital media compared to conventional learning. One way is to use the Sevima Edlink application as a learning medium in class. There are advantages and disadvantages of the Sevima Edlink application from the perspective of teachers and students.